2003
DOI: 10.1590/s0100-40422003000300016
|View full text |Cite
|
Sign up to set email alerts
|

Emprego de monocamadas auto-organizadas no desenvolvimento de sensores eletroquímicos

Abstract: Recebido em 18/7/02; aceito 9/10/02 SELF-ASSEMBLED MONOLAYERS APPLICATIONS FOR THE DEVELOPMENT OF ELECTROCHEMICAL SENSORS. Selfassembled monolayers (SAMs) modified electrodes exhibit unique behavior that can greatly benefit electrochemical sensing. This brief review highlights the applications of SAM modified electrodes in electroanalytical chemistry. After a general introduction, which includes the approaches for SAM development, different electrochemical systems for detecting inorganic and organic species ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
20

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 102 publications
1
18
0
20
Order By: Relevance
“…In this sense, an option that has been widely used in recent decades involves the formation of nanostructured thin films of different materials and their potential application as analytical sensors [1][2][3][4]. The use of modified electrodes with thin films can offer substantial benefits to electroanalysis [5]. These films should be very sensitive when compared to traditional analytical methods, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, an option that has been widely used in recent decades involves the formation of nanostructured thin films of different materials and their potential application as analytical sensors [1][2][3][4]. The use of modified electrodes with thin films can offer substantial benefits to electroanalysis [5]. These films should be very sensitive when compared to traditional analytical methods, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, no study has been reported on the application of modified electrodes with LbL films for PMZ determination. In this sense, the LbL film was formed by using chloride of 3-n-propylpyridinium silsesquioxane (SiPy + Cl À ) and tetrasulphonated phthalocyanine copper (II) (CuTsPc), with the formed film containing five bilayers, designed (SiPy + Cl À /CuTsPc) 5 , as described by de Jesus et al [9]. This modified surface was used to develop an electroanalytical procedure for PMZ determination in commercial formulations using square-wave voltammetry (SWV).…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Desde a década de 1980 o Brasil vem desenvolvendo importantes contribuições na área de eletrodos modificados com vistas ao desenvolvimento de sensores eletroquímicos e tem sido revisada na literatura. [28][29][30][31] Neste contexto, um dos grandes avanços da área consiste na modificação da superfície do eletrodo, o que abriu inúmeras possibilidades para desenvolvimento de sensores e biossensores, contribuindo de modo singular para o avanço da eletroanalítica moderna. 32 A versatilidade dos modificadores (ligantes, polímeros, óxidos, orgânicos, sílicas, metais, complexos, compostos biológicos, enzimas, DNA, proteínas, anticorpos, antígenos, organismos, tecidos, células, organelas, membranas etc.)…”
Section: Eletroanalíticaunclassified
“…8 Em geral, a modificação na superfície eletródica ocorre pela imobilização de grupos funcionais, 12 incorporação de catalisadores inorgânicos 13 e biológicos (enzimas e anticorpos), 14,15 deposição de filmes poliméricos, 16 modificação com sílica 17 e deposição de membranas biológicas. 18 Os eletrodos quimicamente modificados apresentam alta sensibilidade e seletividade; porém, dependendo da modificação realizada podem ocorrer problemas de estabilidade e reprodutibilidade nas respostas voltamétricas, principalmente em meios não aquosos ou em valores de potenciais próximos às reações de eletrólise da água.…”
Section: Eletrodos De Trabalhounclassified